Protection of the IPR (Intellectual Property Rights)for the Culinary Industry through Law No. 30 Of 2000 Concerning Trade Secrets Related to Franchise Agreements Supporting Indonesian Creative Economy Growth - Nurani, Nina; Maya, Yenny; Kaniawati, Keni; Alfiana (International Journal of Psychosocial Rehabilitation, 2020)
The culinary industry is the secret business of innovative recipes in the form of inventions or information as intangible assets that need to have adequate protection of IPR because they have high economic value and are vulnerable to unfair business competition. The purpose of this study is to examine IPR protection for the culinary industry through Law No. 30 of 2000 concerning Trade Secrets and what if they are associated with franchise agreements supporting the growth of the Indonesian creative economy. This study uses a normative juridical approach. Interdisciplinary normative juridical refers to the principles, national legal norms, norms of international law, international conventions as secondary primary data, and reviews of library data. The study uses descriptive research specification qualitative juridical analysis with methods of historical, sociological, systematic legal interpretation and legal construction. The results showed that the Trade Secret Law and franchise arrangements had not been effectively used to provide adequate protection, as evidenced by the high submission of applications for franchise registration not in line with the minimum number of records of transfer documents and licensing agreements at the Directorate General of IPR. In addition, it is not yet well understood, and the regulation is also not yet comprehensive, in the form of unclear categorization and determination of information and legal subject of trade secret owners and ranking level of confidentiality. This opens up the potential for violations in the form of plagiarism and imitation as a form of fraudulent business competition. This has hampered the growth of Indonesia’s creative economy. Therefore, the government needs to revise these various weaknesses and intensify socialization.